Understanding social media addiction from a humanistic perspective : a review - Yeo, Deon Yong (2019)
Social media use is increasing at an alarming rate and has been consistently led by users aged 18 to 29. Similarly, more social media users are finding it difficult to give up social media, raising concerns that social media addiction (SMA) may be growing in the population. Currently, the neurobiological perspective of SMA has been getting more attention in SMA research. In contribution to growing SMA research, this paper reviews whether humanistic theories, namely Maslow’s Hierarchy of Needs and Rogers’ Theory of Self, sufficiently explain the factors associated with SMA - personality traits, impression management, fear of missing out (FoMO) and social comparison - and the consequences of SMA - emotional, relational, health and performance problems. This paper also reviews whether humanistic-existential approaches, namely person-centered, logo and meaning therapies, all of which focus on improving individual decision-making abilities, complement existing therapeutic interventions for SMA and offer new possibilities for the future of SMA treatments.